Transtornos de humor na infância e adolescência: sintomas precoces em filhos de bipolares e traços de temperamento e caráter como endofenótipos na depressão maior - Zappitelli, Marcelo Cardoso [UNIFESP] (2010)
Purpose: To conduct two studies with children and adolescents, aiming to identify psychiatric disorders in the offspring of bipolar parents type I, and to evaluate temperament and character traits in patients with major depressive disorder (MDD). Methods: Study 1: The study involved a case series comprising 35 children and adolescents (20 males/15 females) aged 6 to 17 years (mean age: 12.5±2.9 years). All participants were assessed using the diagnostic interview The Schedule for Affective Disorders and Schizophrenia for School-Age Children – Present and Lifetime Version (K-SADS- PL). Psychiatric family history and demographics were also evaluated. Study 2: A case-control study comprising 41 MDD children and adolescents (8-17 years) matched by gender and age to 40 healthy controls (HC). All participants were diagnostically assessed with the K-SADS-PL. Temperament and character traits were measured by the parent and child versions of The Junior Temperament and Character Inventory (JTCI), and depression severity by The Children’s Depression Rating Scale - Revised (CDRS-R). Results: Study 1: At least one psychiatric disorder was identified in 71.4% of the sample. High rates of specific disorders were noted: mood disorders (28.6%), disruptive behaviour disorders (including attention deficit hyperactivity disorder/ADHD) (40.0%) and anxiety disorders (20.0%). The rate of mood disorders comorbid with disruptive behaviour disorders (17.2%) was higher than the rate of pure mood disorders (11.4%). Presence of psychopathology was commonly reported in second-degree relatives of the offspring (71.4%). Study 2: MDD subjects had significantly higher scores on harm avoidance and novelty seeking dimensions, and lower scores on reward dependence, persistence, self-directedness and cooperativeness compared with HC. Comorbidity with disruptive behaviour disorders exerted influence on almost all dimensions of temperament and character, in general increasing the mean score differences between MDD and HC subjects. Moreover, being currently depressed did not influence the results, except for reward dependence according to parent data. Conclusions: Bipolar offspring are at high risk for developing psychiatric disorders, especially mood and disruptive behaviour disorders. MDD children and adolescents have a different temperament and character profile compared to HC subjects, pointing towards trait-like characteristics of the dimensions harm avoidance and self-directedness.